The insanity file : the case of Mary Todd Lincoln - Neely, Mark E. (Southern Illinois University Press, 1993)
In 1875 Robert Todd Lincoln caused his mother, Mary Todd Lincoln, to be committed to an insane asylum. Based on newly discovered manuscript materials, this book seeks to explain how and why. In these documents- marked by Robert Todd Lincoln as the ""MTL Insanity File""--Exists the only definitive record of the tragic story of Mary Todd Lincoln' s insanity trial. The book that results from these letters and documents addresses several areas of controversy in the life of the widow of Abraham Lincoln: the extent of her illness, the fairness of her trial, and the